2008
DOI: 10.1128/jcm.00258-08
|View full text |Cite
|
Sign up to set email alerts
|

Marked Variability of BK Virus Load Measurement Using Quantitative Real-Time PCR among Commonly Used Assays

Abstract: BK virus (BKV) is the infectious cause of polyomavirus-associated nephropathy. Screening guidelines for renal-transplant recipients define levels of viremia and viruria that are actionable for additional testing or intervention. However, standardized real-time PCR primers, probes, and standards are unavailable, and the extent of agreement among published assays is unknown. We compared seven TaqMan real-time PCR primer/ probe sets (three designed at this institution, three described in the literature, and one p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
105
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 32 publications
1
105
0
3
Order By: Relevance
“…Our findings raise the interesting question of whether different BKV genotypes or subgenotypes exhibit altered tissue tropism or different levels of virulence in vivo. Although previous studies have surveyed BKV genotypes found in nephropathic lesions (15,16,(37)(38)(39), these studies have relied on BKV-I-biased PCR primers that underestimate the abundance of BKV genotypes II, III, and IV (40). The possibility that commonly used PCR primers do not robustly detect non-genotype I BKVs (particularly in the case of individuals coinfected with multiple BKV genotypes) is consistent with our observation that BKV-II seroprevalence (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Our findings raise the interesting question of whether different BKV genotypes or subgenotypes exhibit altered tissue tropism or different levels of virulence in vivo. Although previous studies have surveyed BKV genotypes found in nephropathic lesions (15,16,(37)(38)(39), these studies have relied on BKV-I-biased PCR primers that underestimate the abundance of BKV genotypes II, III, and IV (40). The possibility that commonly used PCR primers do not robustly detect non-genotype I BKVs (particularly in the case of individuals coinfected with multiple BKV genotypes) is consistent with our observation that BKV-II seroprevalence (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Mini-Reviews standard of care for most renal transplant programs, there is no FDA-cleared test, and a number of laboratorydeveloped tests are deployed in clinical laboratories with marked variability in BKV viral load measurements among commonly used tests (21 ). This interassay variability complicates uniform application of BKV screening guidelines.…”
Section: Viral Load Assaysmentioning
confidence: 99%
“…Interlaboratory variability in the PCR assay makes the diagnosis challenging (38), and there is no consensus regarding the level of plasma BK PCR that should be treated. We have little idea as to the natural history of patients with low-level viremia and normal allograft function.…”
Section: What Are Common Strategies In the Diagnosis And Management Omentioning
confidence: 99%